Análise de séries temporais de candidatos às doações de sangue e coletas de sangue realizadas pela fundação Hemominas entre 2005 e 2018. - Elias Melo de Oliveira (2019)
Retrospective longitudinal study with data on blood donations made between 2005 and 2018 at the Hemominas Foundation, which is the main Blood Bank of Minas Gerais, Brazil. Objective: To conduct a systematic review of national and international literature on the subject and to analyze the time series related to blood donation candidates and blood collections performed by the Hemominas Foundation in order to identify the scenario related to blood donations in the state. Methods: Systematic review of national and international literature on blood donations and blood component transfusions with publications from January 1, 2005 to December 31, 2018. With data from the Hemominas Foundation, 10 series were constructed with monthly data related to the number of candidates for blood donation and blood samples taken. The stationarity of the series was verified by the unit root test; the trend by the Cox-Stuart test and seasonality by the Fisher test (significance levels of 10% for the first test and 5% for the last two). Results: The systematic review included 13 studies, which showed an increasing trend in demand for blood components and a decreasing trend in their supply. Of the 10 series created, nine were identified as non-stationary and all series presented the trend and seasonality components. The rate of blood donation candidates and the rate of blood collection performed showed a positive growth trend, with decrease in the last three years. When adjusted for the number of potential blood collections, considering the age-for-donation criterion, the rate of blood collections performed tended to fall steadily over the period. Conclusion: Due to the increasing trend of blood component use in countries more advanced than in Brazil and the reduction of cholesterol in the state of Minas Gerais, which has great representation in the national context, there is a need to reduce the demand for blood components by expanding the use of alternative strategies for blood component transfusions, in addition to conducting new studies on the subject in Brazil.